Cycad-Weevil Pollination Symbiosis Is Characterized by Rapidly Evolving and Highly Specific Plant-Insect Chemical Communication - Salzman, Shayla; Crook, Damon; Calonje, Michael; Stevenson, Dennis W.; Pierce, Naomi E.; Hopkins, Robin (Frontiers in Plant Science, 2021)
Coevolution between plants and insects is thought to be responsible for generating biodiversity. Extensive research has focused largely on antagonistic herbivorous relationships, but mutualistic pollination systems also likely contribute to diversification. Here we describe an example of chemically-mediated mutualistic species interactions affecting trait evolution and lineage diversification. We show that volatile compounds produced by closely related species of Zamia cycads are more strikingly different from each other than are other phenotypic characters, and that two distantly related pollinating weevil species have specialized responses only to volatiles from their specific host Zamia species. Plant transcriptomes show that approximately a fifth of genes related to volatile production are evolving under positive selection, but we find no differences in the relative proportion of genes under positive selection in different categories. The importance of phenotypic divergence coupled with chemical communication for the maintenance of this obligate mutualism highlights chemical signaling as a key mechanism of coevolution between cycads and their weevil pollinators.